Environmental context for the terminal Ediacaran biomineralization of animals. Issue 4 (1st April 2016) - Cui, H.; Kaufman, A. J.; Xiao, S.; Peek, S.; Cao, H.; Min, X.; Cai, Y.; Siegel, Z.; Liu, X.‐M.; Peng, Y.; Schiffbauer, J. D.; Martin, A. J.
Abstract: In terminal Ediacaran strata of South China, the onset of calcareous biomineralization is preserved in the paleontological transition from Conotubus to Cloudina in repetitious limestone facies of the Dengying Formation. Both fossils have similar size, funnel‐in‐funnel construction, and epibenthic lifestyle, but Cloudina is biomineralized, whereas Conotubus is not. To provide environmental context for this evolutionary milestone, we conducted a high‐resolution elemental and stable isotope study of the richly fossiliferous Gaojiashan Member. Coincident with the first appearance of Cloudina is a significant positive carbonate carbon isotope excursion (up to +6‰) and an increase in the abundance and 34 S composition of pyrite. In contrast, δ 34 S values of carbonate‐associated sulfate remain steady throughout the succession, resulting in anomalously large (>70‰) sulfur isotope fractionations in the lower half of the member. The fractionation trend likely relates to changes in microbial communities, with sulfur disproportionation involved in the lower interval, whereas microbial sulfate reduction was the principal metabolic pathway in the upper. We speculate that the coupled paleontological and biogeochemical anomalies may have coincided with an increase in terrestrial weathering fluxes of sulfate, alkalinity, and nutrients to the depositional basin, which stimulated primary productivity, the spread of an oxygen minimum zone, and the development of euxinic conditions in subtidal and basinal environments. Enhanced production and burial of organic matter is thus directly connected to the carbon isotope anomaly, and likely promoted pyritization as the main taphonomic pathway for Conotubus and other soft‐bodied Ediacara biotas. Our studies suggest that the Ediacaran confluence of ecological pressures from predation and environmental pressures from an increase in seawater alkalinity set the stage for an unprecedented geobiological response: the evolutionary novelty of animal biomineralization.